Association of optic nerve sheath diameter with direct intracranial pressure measurement in neurosurgical patients - KC, Bidur; Thapa, Amit (Journal of Kathmandu Medical College, 2022)
Background: Invasive intracranial devices are gold standard for measurement of intracranial pressure (ICP), however optic nerve sheath diameter (ONSD) by using ultrasound is emerging lately as a non-invasive bedside tool. Objectives: This study aimed to find association between ONSD and invasive ICP and also to find optimum cut off of ONSD to detect raised ICP. Methods: An analytical observational study using a convenience sample was done at Department of Neurosurgery, Kathmandu Medical College from March 1, 2022 and March 31, 2022. The ONSD of both the eyes were measured using ultrasound in patients with ventriculostomy catheter. Simultaneous ICP was also recorded. The Pearson’s correlation coefficient was used to assess an association between the ONSD and direct ICP measurement. Results: Total of 40 ONSD measurements were done in 12 neurosurgical patients. Age of patients ranged from 17-75 years with mean age of 47.33 ± 17.67 years with male to female ratio of 1:2 respectively. Pearson’s correlation coefficient of ONSD and invasive ICP was 0.86 (p-value <0.001) showing significant correlation. Receiver operator characteristic curve generated an area under the curve with value of 0.93 (95% of confidence interval = 0.86 to 1.00). The ONSD cut off value of >5 mm predicted ICP >20 mmHg with a sensitivity of 92.3% and specificity of 85.2%. Conclusion: There exists a significant correlation between ONSD and invasive ICP with optimal cut off >5 mm to detect raised ICP.